Social happiness : theory into policy and practice - Thin, Neil (Bristol : Policy, 2012)
An examination of the achievements and potential of applied happiness scholarship in diverse cultures and domains, arguing that progressive policies require a substantial and explicit consideration of happiness.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Social policy; Happiness; Public welfare